2010
DOI: 10.2175/193864710798159101
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of <I>Nitrobacter</I> and <I>Nitrospira</I> Communities in an Aerobic Activated Sludge Bioreactor and their Contributions to Nitrite Oxidation

Abstract: An analysis of nitrite-oxidizing bacteria in the activated sludge process of a full-scale partially nitrifying wastewater treatment plant revealed Nitrospira and Nitrobacter averaged 10 13 cells•L-1 and 10 12 cells•L-1 , respectively. Correlation coefficients linking shifts in NOB community to operational or environmental variables illustrated Nitrospira were negatively correlated to nitrite (r =-0.45, P<0.01), while Nitrobacter showed no significant relationship to nitrite (P=0.1017). Nitrospira was negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…However, Sarioglu et al (2009) observed a higher nitrogen removal of about 85-95 % in an MBR treating domestic wastewater when the DO level was maintained at low level (1.5 mg O 2 L -1 ). Niche-specific adaptation to DO concentration has been observed within the NOB, with Nitrospira demonstrating a negative correlation to DO concentrations (r = -0.46, P \ 0.01), whereas Nitrobacter exhibited a positive correlation (r = 0.38, P \ 0.01) (Huang et al 2010b). Nitrobacter population was also found to increase in winter (low temperatures) and high DO levels ).…”
Section: Dissolved Oxygenmentioning
confidence: 97%
See 1 more Smart Citation
“…However, Sarioglu et al (2009) observed a higher nitrogen removal of about 85-95 % in an MBR treating domestic wastewater when the DO level was maintained at low level (1.5 mg O 2 L -1 ). Niche-specific adaptation to DO concentration has been observed within the NOB, with Nitrospira demonstrating a negative correlation to DO concentrations (r = -0.46, P \ 0.01), whereas Nitrobacter exhibited a positive correlation (r = 0.38, P \ 0.01) (Huang et al 2010b). Nitrobacter population was also found to increase in winter (low temperatures) and high DO levels ).…”
Section: Dissolved Oxygenmentioning
confidence: 97%
“…The nitrification process in wastewater is therefore limited by the AOB and NOB population densities and their physiological activities in different types of WWTPs, including conventional activated sludge treatment systems and MBR (Graham et al 2007;Huang et al 2010b;Zhang et al 2011b). In both cases, the nitrification efficiency seems to be controlled by the prevalent operational and environmental conditions (Manser et al 2005;Bahadoorsingh 2010).…”
Section: Nitrification Processmentioning
confidence: 99%
“…When pure cultures were received, the freeze dried culture was inoculated into 10 mL appropriate medium as suggested by ARS. Paracoccus denitrificans and Pseudomonas putida were inoculated into 10 mL tryptone-glucose-yeast (TGY) media and incubated in the orbital shaker (Forma Scientific, Marjetta, Ohio) at 28C for 24 hours, after which DNA was extracted from pure culture using modified bead beating protocol for DNA extraction (Huang et al 2010;Yu and Mohn, 1999) and stored at -80C for later use.…”
Section: Pure Cultures Culture Media and Growth Conditionsmentioning
confidence: 99%
“…Environmental samples obtained from Michelson Water Reclamation Plant (MWRP) for the ten-month period had DNA directly extracted using published techniques (Huang et al 2010), and were stored at -80 C until analysis. The sampling locations is displayed in Figure 2.…”
Section: Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation